PREPARATION AND SENSORY EVALUATION OF COOKIES SUPPLEMENTED WITH SPINACH (AMARANTHUS GANGETICS) - R, Dhanabaaghyam.; Raga., Keerthini; S, Sanjana.; G, Suganya. (International Journal of Research -GRANTHAALAYAH, 2018)
Spinach [Amaranthus gangetics] leaves were dried in a tray drier at 55°C and ground to pass through 220µm mesh to obtain spinach powder. Micronutrient is rich in Amaranthus gangetics. The spinach has rich source of vitamin C, folate and minerals. The physico-chemical analysis and sensory evaluation was done to know the acceptability of cookies incorporated with red spinach powder. These were evaluated for sensory analysis that included color, flavor, taste, and overall acceptability. The spinach cookies were analyzed for analytical and chemical analysis, which includes moisture content and total ash.